Indeks Massa Tubuh (IMT), Postur Tubuh, Dan Kebugaran Jasmani Anggota PMI Kota Dan Kabupaten Sukabumi - Dikdik Maulana Suparman; Bachtiar Bachtiar; M Saleh (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
The aim of this study was to determine the Body Mass Index (BMI), Posture, and Physical Fitness of PMI City and Sukabumi Members using quantitative methods and data collection techniques were carried out by survey methods on Body Mass Index (BMI), Posture, and Fitness. Physical. The survey method is used to get from certain natural places (not made up) but this study collects data, for example distributing questionnaires, conducting tests and interviewing in a structured way (the treatment is not the same as the experiment). The results of the analysis show that the Body Mass Index of members of the Indonesian Red Cross Volunteer Corps in Sukabumi Regency and members of the KSR PMI of Sukabumi City are mostly in the normal category. The results of the Posture research on members of KSR PMI Sukabumi Regency and PMI Sukabumi City were mostly in good category. Analysis of research data on the level of physical fitness of members of KSR PMI Sukabumi Regency and members of KSR PMI Sukabumi City were mostly in the moderate category.